ASSESSING MULTIREGIONAL ECONOMIC IMPACTS OF ALASKAN FISHERIES: A COMPUTABLE GENERAL EQUILIBRIUM ANALYSIS. Issue 3 (12th July 2014) - Seung, Chang K.; Waters, Edward C.; Leonard, Jerry L.
<x xml:space="preserve">Abstract</x> Alaskan industries, including the seafood industry, are characterized by strong linkages with the rest of the United States, including a large leakage of factor income to, and large imports of goods and services from the rest of the US, especially the West Coast region. This study develops a multiregional computable general equilibrium (MRCGE) model of three US economic regions: Alaska (AK), the West Coast (WC), and the rest of the US (RUS). The model is applied to issues affecting Alaskan fisheries, and is used to calculate the multiregional economic effects, including spread effects, of changes in: (i) the volume of fish caught off AK; (ii) the demand for Alaskan seafood by both the US and the rest of the world; and (iii) currency exchange rates.